INTERNALISASI NILAI-NILAI AGAMA DALAM PEMBENTUKAN KEPRIBADIAN DAN MORAL PADA PENDIDIKAN DASAR - Abdul Wahab Syakhrani (Adisam Publisher, 2025)
This study aims to examine the role of internalising religious values in shaping students' personalities and morals in primary education through a literature review method. Primary education is a crucial phase in a child's development, forming the basis for character and moral development based on religious values. Through a review of various literature and previous studies, this research discusses two main aspects, namely the mechanism of internalising religious values in primary education and the influence of this internalisation on the development of students' personality and morals. The results of the study show that effective internalisation of religious values involves formal learning, teacher role models, and support from the family and community environment. Internalised religious values contribute significantly to the formation of religious character, discipline, responsibility, tolerance, and empathy. Therefore, strengthening the internalisation of religious values must be a top priority in primary education to produce a generation with good character, morals, and religious values.